Development of Liquisolid Technology to Overcome Dissolution/Absorption Limitations of Oral Drugs - Wang, Huan; Zhang, Xingwang (Pharmaceutical Fronts, 2024)
Increasing influx of poorly water-soluble drugs poses a significant challenge to oral drug delivery. Conventional solubilization techniques such as solid dispersion and cyclodextrin inclusion, while capable of improving drug dissolution, suffer from a great predicament in subsequent formulation processing. A novel “powder solution technology,” the liquisolid technique, has come to the forefront in dealing with drug solubilization and formulation of oral “problem” drugs. The liquisolid technique involves the adsorption of liquid medications onto suitable carrier and coating materials, followed by conversion into free-flowing, dry-looking, and compressible powders. In the liquisolid system, the drug is dispersed in an almost molecular state, which greatly contributes to drug dissolution and absorption. This review aims to present the fundamentals of liquisolid technology and update the concept of liquisolid processing to expand its applications. The trend of modern drug discovery, drug solubilization approaches, application of liquisolid technology in formulation innovation, formulation composition, and design of liquisolid systems were discussed in detail. Special emphasis was placed on the application of liquisolid technology to improve the dissolution and bioavailability of poorly water-soluble drugs. Accumulating evidence shows that the liquisolid technology has immense potential to improve oral delivery and facilitate the secondary development of insoluble drugs.
Keywords: liquisolid; poorly water-soluble drugs; dissolution; absorption; bioavailability